THE ROLE OF ISLAMIC EDUCATION IN OVERCOMING YOUTH DISTINCTIONS AT RW 023 KELURAHAN JATI MAKMUR - KECAMATAN PONDOK GEDE KOTA BEKASI - Ristianti Azharita (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
One of the problems often happen in society, such as teenager problem or deliquency, education and social interaction. Now, teenager life is often appeared by the complex problem that need to get attention from all elements. The adolescence is the transitional periode which is past all people from childhood to adult. The condition of teenages has been on transitional periode from childhood to adult periode. They can get consequence, namely can be effected by social media or invironment easily. Because of that, we have to anticipate for minimizing or preventing about teenager problem. Based on it, teenager has to been educated with Islamic education, in order that they can point out kind-personality as teenager and able to avoid immoral action that can damage theirselves and others. And they can show good attitude basen on Islamic education. The purpose of this research is knowing, that is there significant effect between Islamic education on resolve deliquency on RW 023 Kelurahan Jati Makmur Kecamatan Pondok Gede Bekasi. Responden in this research amounted to 46 people.